Challenges and problems in the recruitment of ad hoc workers of election management body at the local level: Evidence from Banyumas - Bowo Sugiarto; Andi Ali Said Akbar; Oktafiani Catur Pratiwi; Indaru Setyo Nurprojo; Titis Perdani (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The prevailing national regulation on the recruitment of PPK, PPS, and KPPS staff sets forth that those temporary officers can be of service for only two periods of general election and cannot be involved afterwards. This regulation actually has positive aspect, but is not easy in its implementation. This article aims at examining the challenges and problems faced by the election management body at local level (Regency KPU) in preparing the human resource of ad hoc staff for the 2019 general election in Indonesia. This article was based on a qualitative research conducted in 2020 in Banyumas Regency, Central Java. This article shows that challenges that had to be faced by Regency KPU in the recruitment of ad hoc employees were the duration of screening and the way village leaders socialized the information regarding the recruitment. Whereas, the involvement of young generation and women as general election ad hoc workers in Banyumas was still low because of a number of factors, from know-how of general election to having lack information of the recruitment. This study concludes that actor’s action choice is limited by a number of matters, such as the path previously taken, rules regulating the agency, and social-political context.